The Degree to which teachers of the first three grades practice distance learning through Darsk platform in Ma’an Governorate in Jordan - Ma'touq, Rania Hamlan Mahmoud (Journal of Curriculum and Teaching Methodology, 2022)
This research aim to determine the degree to which the first three grades teachers practice distance learning through Darsk platform in Ma’an Governorate in Jordan. In order to achieve the research objective, the descriptive analytical approach was adopted by preparing a list for the third grade teachers practices for online learning. Then it was set up in questionnaire form consisting of (29) items encompassing four fields, was distributed to a sample consisted of (230) of male and female teachers in Ma’an Governorat. One of the most important findings of the study is that the degree to which three grades teachers practice distance learning through Darsk platform was medium.Thus, the field of “specialization” ranked first with a medium degree and an arithmetic average of (3.65), followed by The field of "learning and teaching" was at a medium degree with an average score of (3.59), then the field of "learning environment" with a medium degree and an average of (3.49), and the "learning for life" field came in the last rank with a medium degree and an average of (2.43). The results also showed that there were no statistically significant differences in the degree to which teachers of the first three grades practice distance learning through Darsk platform due to the academic qualification in all field. The findings indicated no statistically significant differences in the three grade teachers’ practice for distance learning through Darsk platform of the experience variable and in favor of a category (from 5 years to less than 10 years), and the study came up with several recommendations, the most important of which are: To enroll all teachers of the first three grades in training courses to improve their skills in using e-learning platforms.